2019
DOI: 10.3171/2018.6.jns181099
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transorbital surgery for Meckel’s cave and middle cranial fossa tumors: surgical technique and early results

Abstract: OBJECTIVETumors involving Meckel’s cave remain extremely challenging because of the surrounding complex neurovascular structures and deep-seated location. The authors investigated a new minimal-access technique using the endoscopic transorbital approach (eTOA) through the superior eyelid crease to Meckel’s cave and middle cranial fossa lesions and reviewed the most useful surgical procedures and pitfalls of this approach.METHODSBetween September 2016 and January 2018, the authors performed eTOA in 9 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 41 publications
0
64
0
1
Order By: Relevance
“…3, 4, 5, 6, 7, 8, and 9) [47]. Several variants of these pillar approaches have been described over the last decade in clinical and anatomical studies, each aiming to facilitate surgical goals [8,9,20,24,25,29,33,44,[50][51][52]59]. A thorough understanding of the anatomy of the eyelid is essential in each approach, and possible need for a reconstruction and additional corridors (i.e., multiportal approach) must also be precisely planned before surgery.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…3, 4, 5, 6, 7, 8, and 9) [47]. Several variants of these pillar approaches have been described over the last decade in clinical and anatomical studies, each aiming to facilitate surgical goals [8,9,20,24,25,29,33,44,[50][51][52]59]. A thorough understanding of the anatomy of the eyelid is essential in each approach, and possible need for a reconstruction and additional corridors (i.e., multiportal approach) must also be precisely planned before surgery.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…First, duplicates (n = 89) and non-English abstracts (n = 25) were removed; thereafter, 157 abstracts were screened for relevance resulting in the full-text evaluation of 112 articles. Subsequently, 75 articles were identified for our qualitative synthesis and included case reports (n = 21) , cadaveric studies (n = 32) [3,6,7,10,13,, clinical articles (n = 16) [2,5,8,9,16,[61][62][63][64][65][66][67][68][69][70][71], review of the literatures (n = 3) [72][73][74], as well as technical notes (n = 2) [75,76] and a radiological manuscript (n = 1) [77]. These outlined articles were published between February 1978 and November 2018.…”
Section: Resultsmentioning
confidence: 99%
“…This approach targets the anterolateral and superior region of Meckel's cave. Jeon et al demonstrated in a recent series of nine patients, seven of them with diseases involving Meckel's cave, the feasibility of this novel technique [65]. Even though the sample size is small and the follow-up time was short, the authors reported low morbidity with a single patient suffering of ptosis, which eventually recovered after 6 months.…”
Section: Transorbitalmentioning
confidence: 98%
“…6,7 Their potential for damaging the temporalis muscle and the need for retraction of the temporal lobe have fostered the development of other minimally invasive techniques. 8 During the past decade, other minimal access techniques (ie, transorbital approach, 9 transantral, and modified EEA techniques 10,11 ) to the floor of MCF have emerged.…”
Section: Introductionmentioning
confidence: 99%